Optical investigations of interaction between zinc tetra phenyl porphyrin and CdSe nanoparticles - Lihitkar, N. B.; Singh, S. B.; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Chemical Physics Letters, 2009)
Interactions between nanoparticles of zinc tetra phenyl porphyrin (ZnTPP) with CdSe nanoparticles in dimethyl sulphoxide solvent have been investigated. A ZnTPP-CdSe complex was formed which showed substantial changes in the UV-Vis absorption spectra in the presence of CdSe. Fluorescence measurements showed an interesting behavior at low as well as high concentrations of CdSe. When low concentrations of CdSe nanoparticles were added to the ZnTPP nanoparticles solution, besides two fluorescence bands due to ZnTPP nanoparticles, an intense new band appeared. On the other hand at high concentrations of CdSe one of the fluorescence band of ZnTPP at similar to 604 nm increased. (C) 2009 Published by Elsevier B. V.

Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties

Investigations on optical properties of ZnO decorated graphene oxide (ZnO@GO) and reduced graphene oxide (ZnO@r-GO) - Kumar, Pushpendra; Som, Sudipta; Pandey, Mukesh K.; Das, Subrata; Chanda, Anupama; Singh, Jai (Journal of Alloys and Compounds, 2018)
The present investigation is based on the production of reduced graphene oxide (r-GO) from the graphene oxide using Hummer's (GO) and improved Hummer's methods (IGO) at elaborated conditions, named as GO and IGO, respectively hereafter. In contrast to previously known techniques, the presented process does not generate toxic gas. Meanwhile, the reduction temperature can be easily controlled. This approach provides a more significant amount of hydrophilic oxidized graphene as compared to GO and IGO with the use of additional KMnO4. Thus synthesized IGO was used to produce r-GO by thermal treatment. The morphological characteristics show that the obtained samples have a wrinkled paper-like morphology with severely folded lines. However, r-GO has double layers and multilayer at the edges. All the products (GO, IGO, and r-GO) have been decorated with ZnO nanoparticles (NPs). The XRD patterns of ZnO@GO composites have confirmed the characteristic peaks of wurtzite ZnO indicating the formation of ZnO nanoparticles onto the surface of graphene. The microscopic studies confirm the random growth/decoration of ZnO NPs on the surface of GO/IGO/r-GO sheets. However, in IGO and r-GO, loading/growth of ZnO NPs are less as compared to ZnO@GO. Overall structural studies indicate the oxidation of graphite and reduction of graphene oxide into r-GO sheets and ZnO decoration. Upon UV excitations, a bright blue emission has been exhibited by the GO that originates from geminate recombination of localized e-h pairs in sp(2) clusters those primarily act as the luminescent centers. The noteworthy enhancement in the emission intensities after the incorporation of ZnO nanoparticles on the surface of GO is observed. The improved synthesis method and low-temperature reduction technique of GO may be essential for the large-scale production of r-GO as well as the construction of devices composed of ZnO@GO/IGO/r-GO. (C) 2018 Elsevier B.V. All rights reserved.

Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Comprehensive tutorial on the pulsed laser deposition technique and developments in the fabrication of low dimensional systems and nanostructures - Masood, Khalid Bin; Kumar, Pushpendra; Malik, Mushtaq Ahmad; Singh, Jai (Emergent Materials, 2021)
Pulsed laser deposition (PLD) is a simple and extremely versatile technique to grow thin films and nanomaterials of a wide variety of materials. PLD allows the deposition of profoundly different materials, including high-temperature superconductors, oxides, nitrides, carbides, semiconductors, metals, and even polymers or fullerenes with high deposition rates. Growing thin films using PLD is now being used around the world for prototyping thin films of many inorganic materials and even in device fabrication protocols. This article covers the detailed development, versatility, and reliability of the ultraviolet (UV) excimer laser. It is envisioned that this review article is of interest for both the materials and chemical scientists engaged in more fundamental aspects of pulsed laser ablation and deposition. The present article highlights the historical developments of PLD technique, complete mechanism of thin film fabrication, optimization of the quality of thin films and the fabrication of thin films of the materials like ZnO, Graphene, MoS2, and WS2 which are being explored for various potential applications.